2015
DOI: 10.15184/aqy.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

San rock art: evidence and argument

Abstract: Whether or not a ‘trance-dance’ akin to that of today's Kalahari San (Bushmen) was performed by southern /Xam San in the nineteenth century has long been the subject of intense debate. Here the authors point to parallels between nineteenth-century records of San life and beliefs and twentieth-century San ethnography from the Kalahari Desert in order to argue that this cultural practice was shared by these two geographically and chronologically distant groups. More significantly, it is suggested that these ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The earliest directly dated rock paintings from southern Africa: new AMS radiocarbon dates Later Stone Age (LSA) communities related to the contemporary Bushman (San) peoples of the Kalahari, and it is their ethnography, along with accounts obtained from Bushman informants in the late nineteenth century, that provides the basis for its understanding (Lewis-Williams & Pearce 2004). Research over the past 40 years has shown that the art is most productively and comprehensively explained as the material expression of the powers of ritual specialists (shamans) and of the wider cosmology within which those powers were exercised, often in altered states of consciousness (trance) (Lewis-Williams 1981;Lewis-Williams & Pearce 2004, 2015. This research in southern Africa has influenced rock art studies around the world (e.g.…”
Section: Researchmentioning
confidence: 99%
“…The earliest directly dated rock paintings from southern Africa: new AMS radiocarbon dates Later Stone Age (LSA) communities related to the contemporary Bushman (San) peoples of the Kalahari, and it is their ethnography, along with accounts obtained from Bushman informants in the late nineteenth century, that provides the basis for its understanding (Lewis-Williams & Pearce 2004). Research over the past 40 years has shown that the art is most productively and comprehensively explained as the material expression of the powers of ritual specialists (shamans) and of the wider cosmology within which those powers were exercised, often in altered states of consciousness (trance) (Lewis-Williams 1981;Lewis-Williams & Pearce 2004, 2015. This research in southern Africa has influenced rock art studies around the world (e.g.…”
Section: Researchmentioning
confidence: 99%
“…S. Henshilwood et al, 2011). Furthermore, it has been applied for abstract and figurative mark making on cave and rock walls (Aubert et al, 2018;Dayet et al, 2016;Lewis-Williams & Pearce, 2015). The use of ochre likely emerged during or before the African MSA (C. S. Henshilwood, 2007;C.…”
Section: The Cognitive Affordances Of Ochre Pigmentsmentioning
confidence: 99%
“…Scholars tend to correlate Upper Paleolithic cave depictions with symbolic or religious expressions that might be part of a shamanic practice conducted probably during a state of trance and aimed at a connectedness with the different entities inhabiting the world and the worlds beyond (Arias 2009;Berrocal 2011;Clottes and Lewis-Williams 1998;Lewis-Williams 1997, 2002aLewis-Williams and Clottes 2007;Whitley 2009). However, a general consensus is lacking as to whether the concepts of shamanism and trance contribute to our understanding of Upper Paleolithic cave depictions (Bahn 2001;Helvenston et al 2003;Lewis-Williams 2007;Lewis-Williams and Pearce 2015;McCall 2007;Solomon 2006).…”
Section: Upper Paleolithic Decorated Caves: Towards An Understandingmentioning
confidence: 99%